“Muara” A Musical Composition | ”Muara” Sebuah Komposisi Karawitan - Harys Arya Wibawa; I Wayan Rai S (GHURNITA: Jurnal Seni Karawitan, 2023)
Abstract An estuary is a place where river and sea water meet. One example of an estuary that inspires creators is the estuary at Ketewel Beach, Sukawati, Gianyar, Bali. Based on the inspiration from the estuary of Ketewel Beach, the creator made an innovative musical work entitled "Estuary". In realizing this new work the creator uses the Panca Sthiti Ngawi Sani method which consists of the stages of Inspiration (Ngawirasa), Exploration (Ngawacak), Conception (Planning), Execution (Ngawangun), and Production (Ngebah). After going through cultivation with the above concept, an innovative musical work was created, entitled "Estuary". To realize this work, the creator used the expression media in the form of four gender puppets with slendro barrels, two Krumungan drums, a flute, one Ceng-Ceng Ricik, a Kajar and a pair of Gong Lanang and Wadon. This innovative musical work consists of three parts, namely: the first part describes the atmosphere of a spring from the mountains, the second part describes the atmosphere of a river flow with winding contours, then in the third part describes the meeting between river water and sea water in Ketewel’s estuary. Keywords: Estuary, Method, Works.